The Effects of Florfenicol on the Values of Serum Tumor Necrosis Factor-α and Other Biochemical Markers in Lipopolysaccharide-Induced Endotoxemia in Brown Trout - Ayse Er; Burak Dik (Hindawi Limited, 2014)
The aim of the present study was to determine the effects of florfenicol on the expected changes in sTNF-α, damage markers of the liver and kidney, and the lipid metabolism parameters in endotoxemic brown trout. Ninety-six brown trout were included in this study. After six of the fish were reserved as the control group, the remaining 90 fish were divided equally into 3 groups as follows: LPS (2 mg/kg, IP), LPS (2 mg/kg, IP) + florfenicol (40 mg/kg, IM), and florfenicol (40 mg/kg, IM). Blood samples were obtained from the tail of the fish at 1.5, 3, 6, 10, and 24 hours. The levels of sTNF-α were determined by ELISA and biochemical markers were evaluated with an autoanalyzer. A significant increase was observed in the values of sTNF-α in the LPS and LPS + florfenicol groups (P<0.05). Significant increases were found in the kidney and liver damage determinants in the LPS and LPS + florfenicol groups (P<0.05). Irregular changes in the lipid metabolism parameters were observed in all the subgroups. In conclusion, florfenicol does not affect the increases of sTNF-α caused by LPS and does not prevent liver or kidney damage; at least, it can be said that florfenicol does not have any evident positive effects on the acute endotoxemia of fish.